Strategi Dosen dalam Mengakomodasi Mahasiswa dengan Gaya Belajar Berbeda pada Perkuliahan Tatap Muka di Jurusan Pendidikan Ekonomi, FKIP, Universitas Halu Oleo - Muhammad Juwantho Lewa (Indo Publishing, 2026)
The diversity of student learning styles—visual, auditory, and kinesthetic—is an undeniable reality in face-to-face learning in higher education. Each student has different learning preferences, which require varied teaching strategies to ensure effective learning and achieve the expected objectives. This research is motivated by the fact that some lecturers still apply monotonous teaching strategies without considering the diversity of student learning styles, resulting in teacher-centered learning that fails to accommodate individual student needs.The aim of this study is to identify and analyze the strategies implemented by lecturers in accommodating students with different learning styles in face-to-face learning at the Economic Education Department, FKIP, Universitas Halu Oleo. This study employed a qualitative descriptive approach with 4 lecturers and 60 students from three study programs within FKIP Universitas Halu Oleo as subjects. Data were collected through face-to-face classroom observations, in-depth interviews, and VARK learning style questionnaires. The results showed that lecturers implemented three main strategies: (1) varied teaching methods (interactive lectures, group discussions, and hands-on practice) to accommodate visual, auditory, and kinesthetic learning styles; (2) utilization of diverse learning media (presentation slides, videos, teaching aids, and whiteboards) to reach all learning styles; and (3) providing flexibility in assignments and assessments. Students reported that the variation in teaching methods and learning media helped them understand the material better and increased their learning motivation. This study concludes that differentiation strategies based on learning styles are effectively implemented in face-to-face learning and are recommended as good practices for inclusive education at the Economic Education Department, FKIP, Universitas Halu Oleo.